Land as pedagogy: Nishnaabeg intelligence and rebellious transformation - Simpson, Leanne Betasamosake (Decolonization: Indigeneity, Education & Society, 2014)
A resurgence of Indigenous political cultures, governances and nation-building requires generations of Indigenous peoples to grow up intimately and strongly connected to our homelands, immersed in our languages and spiritualities, and embodying our traditions of agency, leadership, decision-making and diplomacy. This requires a radical break from state education systems – systems that are primarily designed to produce communities of individuals willing to uphold settler colonialism. This paper uses Nishnaabeg stories to advocate for a reclamation of land as pedagogy, both as process and context for Nishnaabeg intelligence, in order to nurture a generation of Indigenous peoples that have the skills, knowledge and values to rebuild our nation according to the word views and values of Nishnaabeg culture.
Keywords: amériques; approches et analyses; canada; cours; discipline; environnement; féminisme autochtone; histoire et politique; nishnaabeg; pol4105; premier cycle; premières nations; pédagogie; pédagogie nishnaabeg; régions géographiques; résistance; résurgence; savoirs autochtones; sciences de l'éducation; sciences humaines; sociologie; système colonial; systèmes d'oppressions; systèmes éducatifs; territoire nishnaabeg; thématiques; éducation par le territoire

Visual representation of gender in flood coverage of Pakistani print media - Ali, Zarqa S. (Weather and Climate Extremes, 2014)
This paper studies gender representation in the visual coverage of the 2010 floods in Pakistan. The data were collected from flood visuals published in the most circulated mainstream English newspapers in Pakistan, Dawn and The News. This study analyses how gender has been framed in the flood visuals. It is argued that visual representation of gender reinforces the gender stereotypes and cultural norms of Pakistani society. The gender-oriented flood coverage in both newspapers frequently seemed to take a reductionist approach while confining the representation of women to gender, and gender-specific roles. Though the gender-sensitive coverage displayed has been typical, showing women as helpless victims of flood, it has aroused sentiments of sympathy among readers and donors, inspiring them to give immediate moral and material help to the affected people. This agenda set by media might be to exploit the politics of sympathy but it has the effect of endorsing gender stereotypes.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; cinéma; communication; discipline; environnement; inondations; médias; pakistan; patriarcat; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; stéréotypes de genre; systèmes d'oppressions; thématiques

Idle No More: identité autochtone actuelle, solidarité et justice sociale : Entrevue avec Melissa Mollen Dupuis et Widia Larivière - Gentelet, Karine (Nouvelles pratiques sociales, 2014)
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; cours; discipline; droit; droits des femmes*; environnement; féminisme autochtone; militance; pol4105; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; science politique et droit; thématiques

Combattre maintenant les inégalités sexuées, sociales et territoriales dans les quartiers politique de la ville et dans les territoires ruraux fragilisés - Haut Conseil à l'Égalité entre les femmes et les hommes (2014)
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; discipline; environnement; europe; france; inégalités; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; systèmes d'oppressions; thématiques; travail; urbanisme

L'écologisme des pauvres une étude des conflits environnementaux dans le monde - Martinez-Alier, Juan; Dufumier, Marc; Verkaeren, André. (Les Petits Matins : Institut Veblen pour les réformes économiques, 2014)
"L'écologie, un luxe réservé aux pays riches? Rien de plus faux, explique Joan Martinez Alier, qui prouve à travers ce livre que justice sociale et préservation de l'environnement, loin de se concurrencer, vont de pair. À rebours de la croyance selon laquelle il faudrait avoir atteint un certain niveau de confort pour se " permettre " d'être écologiste, l'auteur montre qu'il s'agit souvent d'une question de vie ou de mort pour les plus démunis. Ainsi, tout comme il existe un écologisme de l'abondance (le tri sélectif ne peut s'inventer que dans des endroits où les poubelles débordent!), il existe partout dans le monde un écologisme des pauvres. Car non seulement les pauvres dépendent étroitement de leur environnement pour survivre, mais c'est aussi vers eux que sont transférées les activités les plus polluantes. Dans ce livre devenu un classique de l'écologie politique, Joan Martinez Alier s'interroge sur les calculs possibles pour déterminer un prix "écologiquement correct " intégrant les dégâts environnementaux et sociaux. Mais, bien au-delà, il insiste sur l'incommensurabilité des valeurs : quel prix donner à une vie humaine? Quel prix pour une terre " sacrée " détruite par une mine de cuivre. ou pour une communauté entière exposée à des déchets toxiques? Aujourd'hui, petit à petit, la notion de justice environnementale fait son chemin. L'idée de dette écologique également : ceux qui utilisent le moins de ressources ne seraient-ils pas les créanciers de ceux qui les gaspillent? Autrement dit, les riches n'auraient-ils pas une dette écologique envers les pauvres?" Présentation de l'éditeur.
Keywords: approches et analyses; capitalisme; com5170; cours; discipline; environnement; histoire et politique; justice sociale; premier cycle; privilèges; sciences de la gestion; système colonial; systèmes d'oppressions; thématiques; écologie; écologie politique; économie; économie écologique

A question for women's health: Chemicals in feminine hygiene products and personal lubricants - Nicole, Wendee (Environmental Health Perspectives, 2014)
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; corps; environnement; perturbateurs endocriniens; produits d'hygiène féminine; produits toxiques; projet charge mentale; périodes historiques; régions géographiques; santé; thématiques; états-unis